2012
DOI: 10.1186/1479-5868-9-98
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor play among children in relation to neighborhood characteristics: a cross-sectional neighborhood observation study

Abstract: BackgroundAlthough environmental characteristics as perceived by parents are known to be related to children’s outdoor play behavior, less is known about the relation between independently measured neighborhood characteristics and outdoor play among children. The purpose of this study was to identify quantitative as well as qualitative neighborhood characteristics related to outdoor play by means of neighborhood observations.MethodsQuestionnaires including questions on outdoor play behavior of the child were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 36 publications
(46 reference statements)
3
85
1
3
Order By: Relevance
“…Both perceived and objective methods (audits (7 studies) and GIS (12 studies)) were used to measure attributes of the neighbourhood environment. The spatial range of the audits included street blocks [32,40], census blocks [36,43], neighbourhood [50], school attendance boundaries [39] and a quarter-mile (400 m) route from home to nearest nonresidential destination [31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both perceived and objective methods (audits (7 studies) and GIS (12 studies)) were used to measure attributes of the neighbourhood environment. The spatial range of the audits included street blocks [32,40], census blocks [36,43], neighbourhood [50], school attendance boundaries [39] and a quarter-mile (400 m) route from home to nearest nonresidential destination [31].…”
Section: Resultsmentioning
confidence: 99%
“…Half of the studies were from North America (12 from the USA, one from Canada) [31][32][33][34][35][36][37][38][39][40][41][42][43], four were from Australia [44][45][46][47], three from the Netherlands [48][49][50], two from Belgium [51, 52•] and one each from the UK [53•], Portugal [54], Spain [55] and Norway [56]. The majority of the studies (n=22) included crosssectional analyses only; four studies included a prospective design [33, 48, 49, 53•] and two included both crosssectional and prospective analyses [33,48].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A single study examining the association between parent perceived neighborhood safety and children's cognitive development found no association (Kiernan et al, 2008). In young children, the amount of outdoor play as well as the time spent outside unaccompanied at the front of the house or on the street was negatively associated with street traffic (Hüttenmoser, 1995;Aarts et al, 2012), however most studies reported no association between features of neighborhood safety (e.g., safety from traffic and crime) and measures of outdoor play and physical activity (Burdette and Whitaker, 2005;Kimbro et al, 2011;De Vries et al, 2010;Sallis et al, 2002;Timperio et al, 2004).…”
Section: Safetymentioning
confidence: 97%